Naringin attenuates the development of carrageenan-induced acute lung inflammation through inhibition of NF-κb, STAT3 and pro-inflammatory mediators and enhancement of IκBα and anti-inflammatory cytokines - Ahmad, Sheikh Fayaz; Attia, Sabry M.; Bakheet, Saleh A.; Zoheir, Khairy M. A.; Ansari, Mushtaq Ahmad; Korashy, Hesham M.; Abdel-Hamied, Hala E.; Ashour, Abdelkader Elbadawy Abbas; Abd-Allah, Adel R. A. (Springer Nature Switzerland AG., 2015)
Naringin has been reported to possess diverse pharmacological properties, including anti-arthritic and anti-inflammatory activities. The aim of the present study was to determine the potential anti-inflammatory effect of naringin in a mouse model of carrageenan-induced pleurisy. A single dose of naringin (40 and 80 mg/kg) was administered per oral (p.o.) 1 h before carrageenan (Cg) administration. Pro- and anti-inflammatory cytokines were analysed in pleural fluid. We also assessed the effects of naringin on the expression levels of iNOS, inducible cyclooxygenase isoform (COX-2), ICAM-1, MIP-2, PGE2, STAT3, TGF-β1, nuclear factor kappa B (NF-κB) and inhibitor of kappa B (IκBα) in lung tissue. The histological examinations revealed anti-inflammatory effect of naringin while Cg group deteriorated. Naringin downregulated Th1 and upregulated Th2 cytokines. Western blot analyses revealed increased protein expression of NF-κB, STAT3 and COX-2 and decreased IκBα in response to Cg treatment, which were reversed by the treatment with naringin. In the Cg group, mRNA expression levels of pro-inflammatory mediators upregulated and anti-inflammatory mediators downregulated. Naringin reversed these actions.